The Role of Academic Community Service in Increasing Voter Participation in Regional Head Elections in the Madura Islands Region - Mohammad Hidayaturrahman; Ahmad Hasan Ubaid (Abhakte Jurnal Pengabdian Kepada Masyarakat, 2025)
Low voter turnout in regional head elections does not invalidate the election results, but it does reduce the quality of direct democracy. This community service program is an effort by university academics to increase voter participation in the regional head elections, which will be held directly and simultaneously in November 2024. The community service program focuses on the Madura Islands, specifically the Kangean and Sapeken Islands, which are among the furthest regions from Madura. The community service program is conducted in remote villages in the Kangean Islands, such as Batu Putih Village, Cangkaramaan Village, Tembayangan Village, Pajennangger Village, Saobi Village, Sadulang Village, and several other villages in the Arjasa, Kangayan, and Sapeken Districts. The community service program uses a dialogic communication approach, conducted door-to-door, or directly visiting prospective voters at theirs homes. The results show that voters in the islands and remote villages are happy to receive political education and outreach activities from academics. It is hoped that this can also be implemented by local governments, election organizers and supervisors, both the General Elections Commission (KPU) and the Elections Supervisory Agency (Bawaslu). So that in the future, government institutions, organizers and supervisors as well as political parties can carry out political education directly at the homes of citizens/voters.